Anti-corrosion and conductivity of titanium diboride coating on metallic bipolar plates. (1st July 2020) - He, R.Y.; Jiang, J.; Wang, R.F.; Yue, Y.; Chen, Y.; Pan, T.J.
Highlights: TiB2 coating is fabricated on 304SS bipolar plates by the HEMAA technique. TiB2 coating is effective for improving corrosion resistance and conductivity of bipolar plates. Corrosion is evaluated in both the anodic and cathodic environments of PEMFCs. TiB2 -coated 304SS maintains effective conductivity after corrosion test. Abstract: Titanium diboride (TiB2 ) coatings are fabricated on 304 stainless steel bipolar plates using a cost-effective, high-energy micro-arc alloying technique to enhance their corrosion resistance and conductivity. Both the coated and bare bipolar plates are electrochemically tested in solutions to simulate the cathode and anode working environments of the proton exchange membrane fuel cell, namely 0.3 M H2 SO4 and 2 ppm HF with air or hydrogen gas bubbled through. It is found that the compact TiB2 coating with metallurgical bonding to the substrate obviously increases the substrate corrosion potential in both the cathode and anode. Meanwhile, the coating significantly decreases the corresponding corrosion current density of the cathode and anode by three to four orders of magnitude compared to the substrate. The impedance and open circuit potential of the TiB2 -coated steels during long-term immersion are significantly higher than those of the substrate. Furthermore, the contact resistance of the TiB2 -coated sample after corrosion remains 19 mΩ cm 2, which is lower than that of the bare steel. Therefore, TiB2 coating is demonstrated as a promising alternative for enhancing the corrosion resistance and conductivity of bipolar plates, owing to its high chemical stability and effective conductivity.